1972
DOI: 10.3949/ccjm.39.3.125
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal cystic lymphangioma: Report of two cases and review of the literature

Abstract: Cystic lymphangiomas (cystic hygromas) are comparatively rare tumors. Seventy-five percent of these lesions are in the neck, 20% are in the axillary region, and 5% are in the mediastinum, retroperitoneal region, pelvis, or groin. Rarest are retroperitoneal cystic lymphangiomas. Beahrs et al 1 reported nine cases of such tumors diagnosed at the Mayo Clinic from 1911 to 1947. Rauch 2 found 22 cases of retroperitoneal lymphangiomas reported before 1959. Kafka and Novak 3 added 10 cases and reported one of their o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Many authors characterize CL as an abnormality of infancy and childhood [3,1 I], whereas the results of other studies [2, indicate that the CL, when located in the retroperitoneum, may occur in patients of all ages, and of both sexes [4].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Many authors characterize CL as an abnormality of infancy and childhood [3,1 I], whereas the results of other studies [2, indicate that the CL, when located in the retroperitoneum, may occur in patients of all ages, and of both sexes [4].…”
Section: Discussionmentioning
confidence: 84%
“…Others favor a congenital origin, due to proliferation of remnants of the embryonic lymph sac, for unknown reasons [8]. The most widely accepted theory is that of early developmental sequestration of lymphatic vessels that fail to establish connection with normal draining lymphatics and become markedly dilated under the pressure of accumulating lymph [4]. This hypothesis does not account, however, for the often invasive character of CL; in addition, an active growth of endothelium may exist, resulting in slow dissection through normal tissues and pressure atrophy of adjacent structures [9]: It is also possible that the nature of tissue surrounding a lymphangioma may determine its type.…”
Section: Casementioning
confidence: 99%
See 2 more Smart Citations
“…A recent study series showed that they usually affect boys, with a male-to-female ratio of 5:2 and a mean age of presentation of 2.2 years 2. These lesions can be associated with specific genetic abnormalities, most notably Turner syndrome 3. Intra-abdominal cystic lymphangioma is particularly rare, accounting for 2–8% of all cases and the symptoms are variable 4.…”
Section: Discussionmentioning
confidence: 99%